The study of cisplatin and vinorelbine in metastatic uterine cervical cancer - Kamnerdsupaphon P. (2014)
Objective: To determine the therapeutic efficacy of cisplatin in combination with vinorelbine in the treatment of patients with metastatic cervical cancer. Material and Method: a total of 17 patients were enrolled in the present study. The median age was 46 years (38-65). There were 6 patients who were diagnosed as stage IVB cervical cancer without previous treatment. The patients were planned to receive cisplatin 80 mg/m2 on day 1 and vinorelbine at 30 mg/m2 on day 1 and 8 every 3 weeks. Results: Fifteen patients were available for evaluation: 2 (13.3%) achieved a complete response, 8 (53.4%) partial responses, 3 (20%) stable diseases and 2 (13.3%) progression of the disease. Myelosuppression was the major toxicity. Grade 3-4 toxicities include 66.7% hemoglobin and 26.7% neutropenia. No other significant side effects were found. Conclusion: Cisplatin-vinorelbine is an active and well-tolerated regimen in metastatic cervical carcinoma. These results require confirmation.